(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the phenomenon of a student’s deontological culture as an integrative quality of personality that determines the success of their professional development. Based on a systematic approach, the author constructs a model for the actualization of deontological values within the university’s educational space.